Entrepreneurial motivation and self employment intention: a case study on management undergraduates of university of Jaffna - Achchuthan, S.; Nimalathasan, B. (My University, 2012)
This Study presents a new model of entrepreneurial motivation and examines the impact / influence of entrepreneurial motivation on self employment intention. Both quantitative and qualitative approach were utilized in this study, in the quantitative approach, the desirability of self employment, feasibility of self employment, tolerance for risk and perceived government Support to predict intentions for self employment was examined in a sample of 117 management undergraduates at University of Jaffna, Sri Lanka. In the qualitative approach, especially three final year students (one male & two female students) and three scholars in the entrepreneurship academic field (Two male senior lecturers & one female senior lecture) from the Faculty of Management Studies and Commerce were interviewed by the researcher with the help of the structured questions. Separate questions for students and scholars who are involved in the entrepreneurial field were prepared by the researcher to support to the findings of quantitative analysis. Based on the quantitative and qualitative study, the entrepreneurial intention level of the management undergraduates are in the weakest level. There are so many barriers for the lowest level of intention, such as problems in the financial assistance, lack of infrastructure facilities, lack of technological facilities, lack of awareness in the entrepreneurial field, lack of support from governmental and nongovernmental organizations in the Jaffna district, cultural burdens, lack of research focus in the entrepreneurial field etc. Based on the findings from both quantitative and qualitative approach, we recommend to the government, non government organization, financial institutions, educators, and policy makers to provide the financial, marketing, social, technological infrastructures to the management undergraduates to enhance the entrepreneurial intention level.